Peran Koperasi Wanita “Binangkit” dalam Memberdayakan Ekonomi Wanita - Viska Nurul; Luk-luk Atin Marfuah (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper aims to analyze women's economic empowerment carried out by community financial institutions namely cooperatives, specifically the focus of this research is directed to find out the programs in this cooperative and the efforts that are made in empowering the economy of women, as well as the results that have been achieved. This paper is a qualitative research using descriptive methods. Data collection techniques used are observation, interviews, and documentation. Data analysis is carried out through the interpretation of logic connected with the context of Islamic Community Development. The results showed that the empowerment program was carried out by the women's cooperative "Binangkit". By providing home-based business training to mothers and providing assistance in the form of business capital loans also developed businesses that were owned by mothers who were members of this cooperative. In general, it can be concluded that the Role of Women's Cooperatives "Binangkit" in Empowering Women's Economy is quite successful, although there are still many obstacles. With the activities of the cooperative, it is able to change the economy of the community for the better, because many housewives have started their home businesses.